Racial and Ethnic Differences in the Predictive Validity of the Level of Service Inventory–Revised Among Prison Inmates. (March 2015) - Chenane, Joselyne L.; Brennan, Pauline K.; Steiner, Benjamin; Ellison, Jared M.
The Level of Service Inventory–Revised (LSI-R) is a risk/needs assessment tool that is widely used in correctional settings. Extant research has demonstrated the predictive validity of the LSI-R for individuals under correctional supervision. Yet, few researchers have assessed whether the LSI-R and its various subcomponents predict prison misconduct similarly for White versus non-White inmates. Using data collected from male inmates confined in prisons across a Midwestern state, we examined the predictive validity of the LSI-R and its 10 subcomponents for White, Black, and Hispanic inmates. We found that the LSI-R predicted the prevalence of misconduct for inmates of varying races/ethnicities. However, we reached a different conclusion when we examined the incidence of misconduct; the LSI-R composite score and subcomponent scores showed greater predictive utility for White inmates than for non-White inmates. Our findings add to a growing body of research that suggests that the predictive validity of the LSI-R differs by offender race/ethnicity. We discuss the policy implications of our findings and offer recommendations for future research.